Validation of a UPDRS-/MDS-UPDRS-based definition of functional dependency for Parkinson's disease. (July 2020) - Ramsay, Neil; Macleod, Angus D.; Alves, Guido; Camacho, Marta; Forsgren, Lars; Lawson, Rachael A.; Maple-Grødem, Jodi; Tysnes, Ole-Bjørn; Williams-Gray, Caroline H.; Yarnall, Alison J.; Counsell, Carl E.; ,; et al.
Abstract: Introduction: Functional dependency in basic activities of daily living (ADLs) is a key outcome in Parkinson's disease (PD). We aimed to define dependency in PD, using the original and MDS versions of the Unified Parkinson's Disease Rating Scale (UPDRS). Methods: We developed two algorithms to define dependency from items of UPDRS Part 2 and MDS-UPDRS Part 2 relating to basic ADLs (feeding, dressing, hygiene and walking, and getting out of a chair). We validated both algorithms using data from 1110 patients from six community-based PD incidence cohorts, testing concurrent validity, convergent validity, and predictive validity. Results: Our optimal algorithm showed high specificity and moderate to high sensitivity versus Schwab & England <80% (specificity 95% [95% confidence interval (CI) 93–97] and sensitivity 65% [95% CI 55–73] at baseline; 88% [95% CI 85–91] and 85% [95% CI 79–97] respectively at five-years follow-up). Convergent validity was demonstrated by strong associations between dependency defined by the algorithm and cognition (MMSE), quality of life (PDQ39), and impairment (UPDRS part 3) (all p < 0.001). Algorithm-defined dependency status also predicted mortality: HR for mortality in those dependent vs independent at baseline was 1.6 (95%CI 1.2–2.1) and in those dependent vs independent at five-years' follow-up was 2.2 (1.6–3.0). Discussion: We have demonstrated the concurrent validity, convergent validity, and predictive validity of a UPDRS-/MDS-UPDRS-based algorithm to define functional dependency in PD. This can be used for studying dependency in any study where UPDRS or MDS-UPDRS part 2 data have been collected. Highlights: Functional dependency is an important outcome in Parkinson's disease. We have defined dependency based on the UPDRS/MDS-UPDRS scale. We have demonstrated its concurrent, convergent, and predictive validity.